A holistic measurement model of movement competency in children. Issue 5 (3rd March 2016) - Rudd, J.; Butson, M.L.; Barnett, L.; Farrow, D.; Berry, J.; Borkoles, E.; Polman, R.
Abstract: Different countries have different methods for assessing movement competence in children; however, it is unclear whether the test batteries that are used measure the same aspects of movement competence. The aim of this paper was to (1) investigate whether the Test of Gross Motor Development (TGMD-2) and Körperkoordinations Test für Kinder (KTK) measure the same aspects of children's movement competence and (2) examine the factorial structure of the TGMD-2 and KTK in a sample of Australian children. A total of 158 children participated ( M age = 9.5; SD = 2.2). First, confirmatory factor analysis examined the independent factorial structure of the KTK and TGMD-2. Second, it was investigated whether locomotor, object control and body coordination loaded on the latent variable Movement Competency. Confirmatory factor analysis indicated an adequate fit for both the KTK and TGMD-2. An adequate fit was also achieved for the final model. In this model, locomotor ( r = .86), object control ( r = .71) and body coordination ( r = .52) loaded on movement competence. Findings support our hypothesis that the TGMD-2 and KTK measure discrete aspects of movement competence. Future researchers and practitioners should consider using a wider range of test batteries to assess movement competence.